Next-Generation Sequencing Analysis Reveals Novel Pathogenic Variants in Four Chinese Siblings With Late-Infantile Neuronal Ceroid Lipofuscinosis - Ren, Xiao-Tun; Wang, Xiao-Hui; Ding, Chang-Hong; Shen, Xiang; Zhang, Hao; Zhang, Wei-Hua; Li, Jiu-Wei; Ren, Chang-Hong; Fang, Fang (Frontiers in Genetics, 2019)
Neuronal Ceroid Lipofuscinoses (NCLs) are progressive degenerative diseases mainly affect brain and retina. They are characterised by accumulation of autofluorescent storage material, mitochondrial ATPase subunit C or sphingolipid activator proteins A and D in lysosomes of most cells. Heterogenous storage material in NCLs is not completely disease-specific. Most of CLN proteins and their natural substrates are not well characterized. Studies have suggested variants of Late-Infantile NCLs (LINCLs) include the major type CLN2 and minor types CLN5, CLN6, CLN7 and CLN8. Therefore, combination of clinical and molecular analysis has become a more effective diagnosis method. We studied 4 late-infantile NCL siblings characterised by seizures, ataxia as early symptoms, followed by progressive regression in intelligence and behaviour, but mutations are located in different genes. Symptoms and progression of 4 types of LINCLs are compared. Pathology of LINCLs is also discussed. We performed Nest-Generation Sequencing on these phenotypically similar families. Three novel variants c.1551+1insTGAT in TPP1, c.244G>T in CLN6, c.554-5A>G in MFSD8 were identified. Potential outcome of the mutations in structure and function of proteins are studied. In addition, we observed some common and unique clinical features of Chinese LINCL patient as compared with those of Western patients, which greatly improved our understanding of the LINCLs.